2014
DOI: 10.1016/j.exger.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Fatigability of the dorsiflexors and associations among multiple domains of motor function in young and old adults

Abstract: Declines in neuromuscular function, including measures of mobility, muscle strength, steadiness, and patterns of muscle activation, accompany advancing age and are often associated with reduced quality of life and mortality. Paradoxically, older adults are less fatigable than young adults in some tasks. The purpose of this study was to determine the influence of age on fatigability of the dorsiflexors and to evaluate the ecological validity of this test by comparing it to motor function subdomains known to dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 59 publications
(78 reference statements)
2
27
3
1
Order By: Relevance
“…In contrast to the absence of an association between walking endurance and the test of performance fatigability used by Justice et al (30), another measure of fatigue has been found to be associated with walking endurance in old adults. In a sample of 1,155 adults (65-102 yrs), Vestergaard et al (70) examined the association between fatigue and physical function by categorizing participants into those who self-reported elevated levels of fatigue and those who did not.…”
Section: Human Performance and Fatiguecontrasting
confidence: 62%
See 2 more Smart Citations
“…In contrast to the absence of an association between walking endurance and the test of performance fatigability used by Justice et al (30), another measure of fatigue has been found to be associated with walking endurance in old adults. In a sample of 1,155 adults (65-102 yrs), Vestergaard et al (70) examined the association between fatigue and physical function by categorizing participants into those who self-reported elevated levels of fatigue and those who did not.…”
Section: Human Performance and Fatiguecontrasting
confidence: 62%
“…Given that walking endurance provides a clinically relevant measure of human performance, Justice et al (30) compared the associations between walking endurance and measures of neuromuscular function in young (22 ± 4 yrs) and old (75 ± 6 yrs) adults. Of particular interest was the strength of the association between walking endurance (500-m walk) and a laboratory test of leg-muscle fatigability.…”
Section: Human Performance and Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, while fatigue does negatively impact on various metrics of balance and posture 5,39,40 , these changes are time-dependent and can tend to dissipate quickly. This raises the possibility that a contributing factor to the increased falls risk in the older adults may be their decreased ability to recover as quickly from the fatiguing intervention as individuals in the other (younger) groups 41,42 . Thus, while all subjects may exhibit declines in function immediately post-exercise, it is the time-course of the recovery period, which may be a determining factor in whether these declines translate to a prolonged increase in falls risk.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the age-related decline in these various parameters, repeated muscular activation does not always lead to greater fatigability in older adults when compared with young adults, and seems to depend on the task. During sustained isometric tasks, older adults are usually less fatigable than young adults (Christie et al 2011), until more advanced ages (Justice et al 2014). However, there are far fewer studies focusing on age-related fatigability for dynamic as compared with isometric contractions.…”
Section: Introductionmentioning
confidence: 99%